Building interfirm leadership: A relational identity perspective. Issue 5 (October 2017) - Hao, Bin; Feng, Yanan; Ye, Jiangfeng
Abstract: While leadership has been recognized as an approach to facilitating network orchestration, little is known about the mechanism through which a hub firm enhances interfirm leadership. Grounded on the theory of social identity and network orchestration, we develop a framework of the enhancement of interfirm leadership, proposing that the tendency of building leadership rests on the hub firm's ability to shape the partners' relational identity. We identify three types of role-adoption that indicate seven actions a hub firm might take to establish such an identity. We suggest that the mechanism through which leadership emerges is contingent on relationship duration, dependence asymmetry, and competition intensity.